AN ANALYSIS OF INDONESIAN EFL PRE-SERVICE TEACHERS’ L2 SPEECH PRODUCTION - Amelia, Riza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
A number of studies have investigated the EFL students’ speaking performance, however, little is known about the mental processes behind the L2 speech production, meanwhile understanding their route of thought could be instrumental in comprehending key factors of their success as well as their failure. The study is expected to reveal some information about the thinking process undertaken by the EFL learners' oral performance in various social settings. The participants of the study were the first-year pre-service students from a state university in Indonesia. Data of the study were elicited through retrospective verbal reports, interviews, and questionnaires based on the role-play of eight scenarios of complaining performance. Through qualitative data analysis, a framework by Levelt (1999) was used to guide the analysis of speech production. The findings revealed that L2 speech production follow several phases, namely, macroplanning, microplanning, grammatical encoding, morphophonological encoding, phonetic encoding, articulation, and monitoring. It seems that L2 speech production is similar to L2 speech production. In addition, it was revealed that the flow of speech processing was not determined by the level of proficiency alone, as a formal speech situation was reported took more thoughtful consideration than a casual one which could likely run fast and automatically.